IJCM_221A: Assessment of Morbidity Patterns among Bus Drivers in Mangaluru - Ramesh Priyanka; Ranjan Roshan; SuvethaSri Sai; Menon Arundathi; Sophola Alister; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Bus drivers suffer from musculoskeletal disorders manifested through tension, pain and decreased work capacity, due to the lack in postural variations and long working hours. Objectives: To study the pattern of morbidities among bus drivers and the factors responsible for the morbidities. Methods: In this cross-sectional study, 100 bus drivers from Mangalore City were included. The sample size was calculated considering prevalence of musculoskeletal disorders as 70.7%, with 15% relative precision, and 95% confidence interval. Institutional Ethics Committee permission was obtained prior to the commencement of the study. Data was analysed using IBM SPSS for windows version 25.0, Armonk, New York, 25.0. Results: Among the 100 participants, 42 complained of one or more perceived musculoskeletal morbidity. The most common musculoskeletal problem was lower back pain (29) and knee pain (29), followed by upper back pain (13) and shoulder pain (9). Hip/thigh pain was the least common (1), followed by neck (3) and wrists/hands (3). Out of the 18 bus drivers with coughs, all of them complained of early morning cough. Clinical assessment revealed reduced visual acuity among 32 subjects, 87% of bus drivers were found to have pre-hypertension and 5% had stage 1 hypertension, 37 were obese and 34 were normal. Conclusion: Musculoskeletal morbidities were found to be the most common among bus drivers, followed by reduced visual acuity.